Endoscopic Assistance in the Deep and Narrow Spaces of the Brain—Microscopic Tumor Surgery Supported by the New Micro-Inspection Tool QEVO® (Technical Note) - Schebesch, Karl-Michael; Doenitz, Christian; Höhne, Julius; Haj, Amer; Schmidt, Nils Ole (Frontiers in Surgery, 2021)
Introduction To evaluate the feasibility and efficacy of the innovative micro-inspection tool QEVO® (Carl Zeiss Meditec, Oberkochen, Germany) as an endoscopic adjunct to microscopes for better visualization of the surgical field in complex deep-seated intracranial tumors in infants and adults. Patients and method We retrospectively assessed the surgical videos of 25 consecutive patients with 26 complex intracranial lesions (timeframe 2018–2020). Lesions were classified according to their anatomical area: 1=sellar region (n=6), 2=intra-ventricular (n=9), 3=IV.ventricle and rhomboid fossa (n=4), and 4=cerebellopontine angle (CPA) and foramen magnum (n=7). Indications to use the QEVO® tool were divided into five ‘QEVO® categories’: A=target localization, B=tailoring of the approach, C=looking beyond the lesion, D=resection control, and E=inspection of remote areas. Results Overall, the most frequent indications for using the QEVO® tool were categories D (n=19), C (n=17), and E (n=16). QEVO® categories B (n=8) and A (n=5) mainly applied to intra-ventricular procedures (anatomical area 2). Discussion The new micro-inspection tool QEVO® is a powerful endoscopic device to support the comprehensive visualization of complex intracranial lesions and thus instantly increases intraoperative morphological understanding. However, its use is restricted to the specific properties of the respective anatomical area.